Contaminación de agua superficial de la periferia urbana de Puerto Maldonado, al sureste de la amazonia peruana - Ibana-Lopez, Karla (2021)
The aim of this study was to evaluate the contamination of surface waters in the urban periphery of Puerto Maldonado (Peruvian Amazon), using biological, physicochemical, and microbiological analyses. The water samples were collected in six water bodies (two rivers, three streams and one lake). The physicochemical parameters of each study site did not exceed the limits of the Peruvian Environmental Quality Standard (ECA), except for dissolved oxygen in rivers near urban areas. Pollution of water resources is related to raw sewage and rainwater runoff. Thus, the highest points of faecal contamination were in rivers near urban areas, exceeding the threshold established by the ECA for the conservation of the aquatic environment (CFU ml-1 >2000). In the Madre de Dios River, the concentration of faecal coliforms exceeded the maximum allowed by the ECA by 75 fold, indicating that the Tambopata and Madre de Dios rivers of Puerto Maldonado are heavily contaminated.